Enhanced Photolumincence and Electrochemical Performance of ZnO/ZnS Coaxial Nanocables - Ahmad, M.; Sun, H.; Nisar, A.; Maaz, K.; Ali, G.; Karim, S. (The Nucleus, 2015)
ZnO based sulfide coaxial nanocables have been prepared by a two-step hydrothermal approach for the investigation of lithium storage capacity. The as-prepared ZnO/ZnS structures are analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray photospectroscopy (XPS), photoluminescence (PL) and by electrochemical work station. It has been found that these nanostructures demonstrate higher initial discharge capacity of 1096 mAhg-1 with a 69% coulombic efficiency at a rate of 120 mAhg-1 between 2 to 0.02 V. In addition, ZnO/ZnS structures show a significantly improved photoluminescence performance as compare with pure ZnO NWs. The enhanced lithium storage capacity and PL performance is ascribed to the coaxial structure of both materials.